1991
DOI: 10.1007/bf01613193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zindoxifene on experimental prostatic tumours of the rat

Abstract: The anti-oestrogen zindoxifene was originally developed as a drug for the treatment of hormone-dependent mammary carcinomas. Experiments with rats bearing androgen-dependent prostatic tumours revealed anti-neoplastic activity of zindoxifene on these tumours also. Therefore, the inhibitory effect of this drug was studied in various prostatic tumour models in comparison to the anti-oestrogen tamoxifen and to castration. The growth of the hormone-dependent Dunning R3327 H tumour was strongly inhibited by zindoxif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Antiestrogens could have an anti-prostate cancer activity, e.g., tamoxifen (Schneider et al 1991;Ryan and Small 2003) and zindoxifene (Schneider et al 1991;. We could show that the shift of the two OH groups in DES into the meta-positions led to a compound with antiestrogenic potency (Kranzfelder et al 1980).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Antiestrogens could have an anti-prostate cancer activity, e.g., tamoxifen (Schneider et al 1991;Ryan and Small 2003) and zindoxifene (Schneider et al 1991;. We could show that the shift of the two OH groups in DES into the meta-positions led to a compound with antiestrogenic potency (Kranzfelder et al 1980).…”
Section: Discussionmentioning
confidence: 78%
“…A survey of Dunning PC models is given by Tennant et al (2000). The used AR + Dunning R3327-H PC is inhibited by cDDP, orchiectomy and other endocrine therapeutic measures like administration of the non-steroidal estrogen DES and the ''partial'' antiestrogen zindoxifene (Schneider et al 1991), but differs from the subtype G (used in the test of meso-1-PtSO 4 ) by a slower tumor cell proliferation rate.…”
Section: Determination Of Tumor Growth Inhibitory Effects On Rat Pcsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is remarkable that zindoxifene was even able to delay the relapse of the Dunning R 3327-H PC by 7 weeks in comparison to castration [29]. Tamoxifen produced only marginal inhibitory effects on this tumor [29].…”
Section: "Partial" Antiestrogens/serms/erˇagonistsmentioning
confidence: 96%
“…A randomized, prospective clinical study on a combination of castration (causing androgen ablation) and cDDP showed that after 6 weeks the number of patients with progressing tumors was much smaller in the group receiving both treatments than in the group with castration alone [26]. Pre-clinical experiments of von Angerer et al [27] revealed that the activity of the "partial" antiestrogen zindoxifene on the androgen receptor-positive (AR + ) Dunning R3327-G PC of the rat -presumably caused by reduction of the androgen level to castration values due to its residual estrogenic potency -could also be enhanced by simultaneous administration of cDDP (to the mode of action of zindoxifene compare Schneider et al [28,29]). …”
Section: Prostate Cancer Therapy With Cddp and Cbdcamentioning
confidence: 98%